D-Amino Acid Oxidase-pLG72 Interaction and D-Serine Modulation - Pollegioni, Loredano; Piubelli, Luciano; Molla, Gianluca; Rosini, Elena (Frontiers in Molecular Biosciences, 2018)
pLG72 is a small, primate-specific protein of 153 amino acids. It is the product of the G72 gene, expressed in testis, spinal cord, and brain. The presence of G72 transcript and pLG72 has recurrently been called into question, however G72 mRNA and pLG72 protein levels were higher in blood and brain of patients with schizophrenia than in healthy controls. On the one hand, the SNP rs2391191 corresponding to the R30K substitution in pLG72 was genetically linked to schizophrenia, reduced thickness of the brain cortex in schizophrenia-affected individuals, and altered memory function. Various lines of evidence indicated that pLG72 is a mitochondrial protein, specifically an extrinsic protein bound on the outer membrane. Over the years, pLG72 was proposed to be involved in different functions: a) overexpression induces mitochondria fragmentation, increasing the numbers of shorter and more mobile ones which could be delivered faster to regions of intense growth and facilitating the dendritic complexity; b) it might induce oxidative stress by interacting with methionine-R-sulfoxide reductase B2; and c) it binds and modulates the activity of FMN-containing oxidoreductase of the respiratory complex I. The main role of this protein, however, is related to its binding to the human flavoenzyme D-amino acid oxidase (hDAAO), i.e., the main catabolic enzyme for D-enantiomer of serine. This D-amino acid is a main endogenous coagonist of the N-methyl-D-aspartate type glutamate receptor (NMDAR) involved in main functions such as synaptic plasticity, learning, memory, and excitotoxicity. For this work, we reviewed the recent literature concerning the hDAAO-pLG72 interaction, focusing on the molecular details of the interaction, the effect of hDAAO function and stability, and the cellular effects, especially on D-serine concentration. The main effects related to the pathological R30K substitution are also reported. We have highlighted the gaps in our knowledge of this human protein as well as the relevance of clarifying the molecular details of hDAAO-pLG72 interaction in order to design molecules to modulate hDAAO activity/stability and thus NMDAR function acting at the D-serine cellular level.